As we know that,
Probability of Event ‘E’=P(E)
Probability of an event ‘not E’ = P(E̅ )
⇒ P(not E) = 1 – P(E)
⇒ P(not E) + P(E) = 1
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :